PENYELESAIAN SENGKETA HUKUM PERKAWINAN ADAT DALAM HARTA BUANG DI DESA SIFNANA KECAMATAN TANIMBAR SELATAN KABUPATEN KEPULAUAN TANIMBAR - Bulurdity, Maria Monica; Murary, Weron; R. Morintoh, Raymond (Ensiklopedia of Journal, 2024)
The purpose of this research is to find out how to resolve customary marriage legal disputes in the property of banishment in Sifnana Village, Tanimbar Islands Regency, and to find answers to the obstacles that occur in the resolution of customary marriage legal disputes in the property of banishment in Sifnana Village, Tanimbar Islands Regency. In accordance with the objectives of the research above, it is hoped that this research can enrich the systematics and appreciation as well as the benefits and input in the resolution of customary marriage legal disputes in the property of banishment in Sifnana Village, Tanimbar Islands Regency. The research used is Normative Empirical research, which uses several approaches whose data sources use primary data and secondary data, and uses a direct or field approach in the community, especially in Sifnana Village, South Tanimbar District, Tanimbar Islands Regency. by collecting data to be used in this research by means of interviews and documentation. by managing research data and analyzing it qualitatively, namely analyzing data based on its quality and then describing it using words so that a language or presentation is obtained in the form of systematic and understandable sentences, then conclusions are drawn from the Tanimbar tribe. The results of the study obtained by the author, in the form of Settlement of Customary Marriage Law Disputes in Harta Buang in Sifnana Village, Tanimbar Islands Regency, can be resolved by means of customary customs that apply in the Tanimbar community, which involves several parties including the male party referred to as duan and the female party as lolat which is a married couple who are about to divorce, in addition to the traditional heads of Nduan and Lolat, parents of the Nduan and Lolat parties who are about to divorce, traditional shops, tribal chiefs can even involve the village head if necessary. These parties play an important role in the implementation of the settlement of customary marriage law disputes in Harta Buang in Tanimbar, especially in Sifnana Village. In addition, it can also be resolved through consultation and negotiation. Therefore, anyone who does not implement it properly and does not comply with the customary traditions that have been applied, the consequences are borne by themselves. In addition, the Tanimbar community must be more in depth in responding to the obstacles in resolving a dispute, especially the customary marriage law dispute in Hartabuang in Sifnanan Village, Kepulawan Tanimbar Regency, so that a resolution of the customary marriage dispute of Hartabuang can run well and smoothly. Although the lack of understanding of customs, Modern influences or the influence of the development of the era in the current era, Lack of communication and openness between the Nduan men and Lolat women, Disacceptance of customary decisions regarding the settlement of customary marriage law disputes of Hartabuang in Sifnana Village, Kepulawan Tanimbar Regency and obstacles in terms of time availability and commitment sometimes make it difficult to gather all parties at the same time.Keywords: Dispute, settlement of discarded property.Tanimbar Islands traditional marriage,Sifnanavillage